2013
DOI: 10.3109/09286586.2013.767355
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Anterior Corneal Astigmatism in Tohono O’odham Native American Infants and Children

Abstract: The greatest change occurred in highly astigmatic infants and toddlers (0.37 D/year). By age 3 years, change was minimal and not clinically significant. Changes observed were due primarily to change in the J0 component of astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The astigmatism is relatively stable from a young age 14 and clearly present before the onset of myopia in most cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The astigmatism is relatively stable from a young age 14 and clearly present before the onset of myopia in most cases.…”
Section: Discussionmentioning
confidence: 97%
“…While there are sometimes minor fluctuations in astigmatic power, anterior corneal astigmatism typically becomes stable by 3 years of age and most astigmatic Tohono O'odham children remain astigmatic throughout childhood. 14 We have assembled a large longitudinal database of refractive error in Tohono O'odham children ranging in age from 3 to 18 years. In the present study, we investigate the hypothesis that degradation of image quality due to refractive astigmatism creates complex cues to emmetropization, resulting in increased rate of spherical equivalent shift towards myopia and increased occurrence of myopia.…”
mentioning
confidence: 99%
“…These data extend our previous longitudinal reports on astigmatism in this population to a much larger age range, allowing us to compare results in younger and older school-age children. 7 In addition, we extend our previous cross-sectional analysis of the relation between refractive astigmatism and its components (keratometric and internal astigmatism) in preschoolers to a larger age range and to a longitudinal sample, 9 allowing us to assess the hypothesis that change in internal astigmatism may be negatively correlated with change in amount of keratometric astigmatism, resulting in stable levels of refractive astigmatism with age.…”
mentioning
confidence: 99%
“…1,2,4-7 A longitudinal study of corneal astigmatism in 960 Tohono O'odham children aged 6 months through 7 years showed that in early development (6 months to <3 years), astigmatism decreased in children with high astigmatism (À0.37 diopters [D]/y) and remained stable in children with little or no astigmatism (þ0.05 D/y). 7 From age 3 through 7 years, astigmatism decreased in children with both high astigmatism (À0.11 D/y) and low/no astigmatism (À0.03 D/y). 7 A detailed account of changes in astigmatism beyond age 7 years in this population has not yet been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation